The Erosion of FAPE for Students with LD. Issue 1 (23rd November 2018) - Calhoon, Mary Beth; Berkeley, Sheri; Scanlon, David
Abstract: How schoolsfulfill Free and Appropriate Public Education (FAPE) requirements has evolved. Decades of general and special education reforms have led to dramatic increases in expectations for students in special education to be included in the general education classroom and curriculum and to achieve to the same high standards as their general education peers. Students with learning disabilities (LD) in particular are impacted by these reforms. The notion of their individually‐appropriate education has been slowly eroded as limitations in special education practices and the goals of education reform have been responded to. As special education intentions and practices advance, stakeholders have a responsibility to protect the FAPE of students with LD, to ensure meeting these students' individualized learning needs.